Oncological care organisation during COVID-19 outbreak - Ahmad Awada; Jean-Pascal Machiels; Sylvie Rottey; Sabino De Placido; Massimo Cristofanilli; Javier Cortes; Miguel Martin; Marco Tagliamento; Marc Peeters; Mario Campone; Concetta Elisa Onesti; Hope S Rugo; et al. (ESMO Open, 2020)
Background COVID-19 appeared in late 2019, causing a pandemic spread. This led to a reorganisation of oncology care in order to reduce the risk of spreading infection between patients and healthcare staff. Here we analysed measures taken in major oncological units in Europe and the USA.Methods A 46-item survey was sent by email to representatives of 30 oncological centres in 12 of the most affected countries. The survey inquired about preventive measures established to reduce virus spread, patient education and processes employed for risk reduction in each oncological unit.Results Investigators from 21 centres in 10 countries answered the survey between 10 April and 6 May 2020. A triage for patients with cancer before hospital or clinic visits was conducted by 90.5% of centres before consultations, 95.2% before day care admissions and in 100% of the cases before overnight hospitalisation by means of phone calls, interactive online platforms, swab test and/or chest CT scan. Permission for caregivers to attend clinic visits was limited in many centres, with some exceptions (ie, for non-autonomous patients, in the case of a new diagnosis, when bad news was expected and for terminally ill patients). With a variable delay period, the use of personal protective equipment was unanimously mandatory, and in many centres, only targeted clinical and instrumental examinations were performed. Telemedicine was implemented in 76.2% of the centres. Separated pathways for COVID-19-positive and COVID-19-negative patients were organised, with separate inpatient units and day care areas. Self-isolation was required for COVID-19-positive or symptomatic staff, while return to work policies required a negative swab test in 76.2% of the centres.Conclusion Many pragmatic measures have been quickly implemented to deal with the health emergency linked to COVID-19, although the relative efficacy of each intervention should be further analysed in large observational studies.